2021
DOI: 10.1155/2021/9979111
|View full text |Cite
|
Sign up to set email alerts
|

Monocular Vision Ranging and Camera Focal Length Calibration

Abstract: The camera calibration in monocular vision represents the relationship between the pixels’ units which is obtained from a camera and the object in the real world. As an essential procedure, camera calibration calculates the three-dimensional geometric information from the captured two-dimensional images. Therefore, a modified camera calibration method based on polynomial regression is proposed to simplify. In this method, a parameter vector is obtained by pixel coordinates of obstacles and corresponding distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…3) The ranging method proposed by Xue [20]. This paper is an in-depth study based on Xue's method, aiming to clarify the effect of camera height on camera calibration and ranging results, so a comparison with Xue's method is also needed.…”
Section: Compare With Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) The ranging method proposed by Xue [20]. This paper is an in-depth study based on Xue's method, aiming to clarify the effect of camera height on camera calibration and ranging results, so a comparison with Xue's method is also needed.…”
Section: Compare With Other Methodsmentioning
confidence: 99%
“…The calibration method proposed by Xue et al [20] links the geometric ranging model and the focal length calibration together, differs from the previous calibration idea of correcting the pixel coordinates with distortion. In this method, the distortion and defocusing phenomena caused by the nonlinear imaging of the camera are innovatively compensated to the focal length of each pixel point, so the focal length of the camera is not considered as a constant value in this calibration method, and the expression of the focal length of a pixel point with its physical coordinates needs to be obtained using polynomial regression.…”
Section: Literature Surveymentioning
confidence: 99%
“…Previous studies have shown that [10], when the height of the monocular surveillance camera and the target feature points are fixed, the pixel coordinates of the ground feature points of the measured object can be converted into world coordinates, thereby calculating the Euclidean distance between the camera and the world coordinates of the target feature points. This article uses Xue Lixia's monocular vision ranging model to derive a two-dimensional positioning model for ground feature points of image targets based on monocular vision.…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently employed in research areas such as visual navigation [3], traffic safety [4], visual obstacle avoidance [5], and others. The two primary visual ranging techniques are monocular vision measurement and stereo vision measurement [6]. By utilizing the parallax concept, stereo vision can measure distance, but accurate feature point matching is challenging and can result in subpar real-time performance [7].…”
Section: Introductionmentioning
confidence: 99%